2020
DOI: 10.48550/arxiv.2003.07502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overlapping Schwarz Decomposition for Constrained Quadratic Programs

Sungho Shin,
Mihai Anitescu,
Victor M. Zavala

Abstract: We present an overlapping Schwarz decomposition algorithm for constrained quadratic programs (QPs). Schwarz algorithms have been traditionally used to solve linear algebra systems arising from partial differential equations, but we have recently shown that they are also effective at solving structured optimization problems. In the proposed scheme, we consider QPs whose algebraic structure can be represented by graphs. The graph domain is partitioned into overlapping subdomains, yielding a set of coupled subpro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Question (Q1) has been recently addressed in specific settings such as nonlinear dynamic optimization [22,24,31,34] and graph-structured quadratic programs [30,33]. Our work generalizes such results.…”
Section: Our Work Is Motivated By the Following Questionsupporting
confidence: 60%
See 1 more Smart Citation
“…Question (Q1) has been recently addressed in specific settings such as nonlinear dynamic optimization [22,24,31,34] and graph-structured quadratic programs [30,33]. Our work generalizes such results.…”
Section: Our Work Is Motivated By the Following Questionsupporting
confidence: 60%
“…Addressing this question is crucial for understanding solution stability of a wide range of problem classes, for designing approximation schemes (often cast as parametric perturbations) [6,13,23,32,34], and for designing solution algorithms [24,30,31]. For instance, it has been recently shown that EDS plays a central role in assessing the impact of coarsening schemes [19,32] for dynamic optimization and in establishing convergence of overlapping Schwarz algorithms for graph-structured problems [24,30,31]. From an application stand-point, our results seek to provide new insights on how perturbations propagate through graphs and on how the problem formulation influences such propagation.…”
Section: Our Work Is Motivated By the Following Questionmentioning
confidence: 99%
“…algebraic modeling capabilities of JuMP.jl (Dunning et al, 2017) and facilitates access to infrastructure modeling tools such as GasModels.jl and PowerModels.jl (Bent et al, 2020;Coffrin et al, 2018). Another key benefit of Plasmo.jl is that it can communicate model structures and this facilitates the implementation of different decomposition strategies such as the alternating direction method of multipliers (Boyd et al, 2011), overlapping Schwarz (Shin et al, 2020a), and parallel interior-point (IP) methods (Chiang et al, 2014;Rodriguez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%